Fabrication of magnetic HAP-GO-PES membrane for cobalt removal: article - Zawawi, Mohamad Sufian; Othman, Nur Hidayati (2018)
A flat sheet type of polyethersulfone (PES) magnetic nanosorbent membrane, hydroxyapatite-coated Fe2O3 nanoparticles (MHAP) with graphene oxide (GO) adsorbent was prepared by using immersion phase inversion process and used for the adsorption and removal of heavy metal ions. The properties of MHAP, GO adsorbent and prepared MHAPGO-PES that had been synthesized were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction and water contact angle measurement. The prepared membrane performance test was carried out using pure water flux and heavy metal removal to identify beneficial effects of adding MHAP and GO to the PES membranes. Due to the nature hydrophilic characteristics of GO, acts as additive to modified polymeric membranes appeared to be more hydrophilic and show higher pure water flux recovery ration than bare membrane. After fabrication, the water flux ratio increases as the concentration of the additives added increases from 18.82 to 324.95 L/m2.hr for pressure at 1 bar. Same as for the pressure at 2 bar, the water flux increase from 17.66 to 396.10 L/m2.hr